INDUSTRIAL RELATIONS DISPUTE CLAIMS TERMINATION BY WORKERS (Case Study of Case Number 972K/Pdt.Sus-PHI/2018) - Sukma Permana, Yana; Saepudin, Aep (Journal Evidence Of Law, 2022)
Indonesia is a state of law, as stated in Article 1 paragraph (3) of the 1945 Constitution, which reads "Indonesia is a State of Law" Law number 13 of 2003 concerning Manpower can be said to be a material law in the field of manpower. material law if there are violations committed against Law number 13 of 2003 concerning Manpower, of course there must be a formal law in enforcing the material law. The Republic of Indonesia number 2 of 2004 concerning the Settlement of Industrial Relations Disputes (UUPPHI). Such as the legal issues of industrial relations disputes, termination of employment that occurred between Teti Sunarti (a worker) and the Central Board of the Association of Indonesian Loading and Unloading Companies (DPP APBMI). In this case, expel workers on the grounds that the General Chairperson of the APBMI DPP is uncomfortable with the presence of workers. Workers ask the DPP APBMI to provide compensation in accordance with the applicable laws and regulations. Problem formulation: 1). How is the settlement of industrial relations disputes regarding termination of employment in the industrial relations court at the Central Jakarta District Court? 2). How is the application of compensation due to termination of employment after the case has permanent legal force? This research uses a normative research type, namely legal research that aims to describe the findings, norms, positive legal principles, legal systematics that have been available and contained in secondary data. The conclusion of the APBMI DPP's action to expel workers without being followed by a legal process resulted in workers suing, as compensation the APBMI DPP must provide compensation to workers in the amount of Rp. 71.200.000 (seventy one million two hundred thousand rupiah).